A eutanásia na visão do garantismo penal - Reicher, Regina Maria (2005)
Comparing euthanasia procedure and guarantee of the Luigi Ferrajoli, as to penal prohibition, the injury and necessity principles, and minimal penal law, this study does a projection regarding main consequences of this conduct in the penal law, notably its consequences to the human dignity principle, which is the logical correspondent of the modern Democratic Law State. The penalization is not required in the model of the minimal penal law defended for the guarantee, not even in a mitigation form, of the human behavior named euthanasia, which must be revised, due to the fact that its your configuration about a prohibited and juridical guilty behavior doesn t match with a modern vision of the penal guarantee, not to mention that the penal law must only appeal as a extreme medicine, as a ultima ratio . In the law guarantee vision, which is based on the human essentials rights for fundamental and the limitation of the state punitive power against the arbitrating and the illegality, leads to the conclusion that the dignity of the death process turns into a new right of the citizen, now, raisen up to the fundamental rights category.